2004
DOI: 10.1097/01.smj.0000060571.56673.0f
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycotic Tumor of the Abdominal Wall

Abstract: We present the case of an elderly patient with abdominal pain, weight loss, and subjective fever in whom a magnetic resonance imaging study revealed a perihepatic abscess without invasion. After drainage, anaerobic cultures yielded Actinomycosis israelii. We discuss Actinomycosis species, with an emphasis on its pathology and multiple presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…There is no doubt that long-term use of an IUCD represents a risk factor for pelvic actinomycosis and potentially for secondary dissemination to a distant site such as in the abdominal wall. The infection rarely disseminates by either lymphatics or the hematogenous route [2, 3, 10]. As in the presented case, the actinomycosis infection was associated with the prolonged use of IUCD (Multiload Cu-375) which has a normal life-span of three to five years.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…There is no doubt that long-term use of an IUCD represents a risk factor for pelvic actinomycosis and potentially for secondary dissemination to a distant site such as in the abdominal wall. The infection rarely disseminates by either lymphatics or the hematogenous route [2, 3, 10]. As in the presented case, the actinomycosis infection was associated with the prolonged use of IUCD (Multiload Cu-375) which has a normal life-span of three to five years.…”
Section: Discussionmentioning
confidence: 65%
“…Actinomycosis is a chronic abscess-forming disease predominantly caused by Actinomyces israelii . Pathologic presentations of actinomycosis include cervicofacial (50% of cases), abdominal (20%), thoracic (20%), and pelvic involvement (15%) [10]. The destruction of mucosal barrier by trauma, operations, immunosuppression, and chronic inflammatory disease is recognized as predisposing factors for the penetration of the bacteria [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 These filamentous bacteria usually colonize the oral cavity, gastrointestinal tract, and vagina. 5,6 A previous theory 4,5 suggested that infection could be secondary to a breakdown in mucosal integrity resulting from surgery (eg, appendectomy) or trauma. However, when the site of the primary abscess is not related to disruption of the mucosal barrier, hematologic spread may be suspected.…”
Section: 3mentioning
confidence: 99%
“…Primary abdominal wall localization is rare; up to 2004 only nine cases have been reported in the English medical literature [13,14] . In our case, the patient reported the use of an IUD in the past with no information about how many years she used it or when it was removed.…”
mentioning
confidence: 99%